CD146-positive adipose-derived stem cells subpopulation enriched by albumin magnetic sphere ameliorates knee osteoarthritis pain and promotes cartilage repair - Lianghao Wu; Xu Zhang; Chengqing Yi; Hanru Ren (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background The use of adipose stem cell (ADSCs) subpopulations in cartilage repair remains poorly characterized. In this study, we constructed an albumin magnetic sphere with specific targeting of CD146 (CD146-AMs) for sorting a subpopulation of CD146-positive ADSCs (CD146 + ADSCs) and explored the role of CD146 + ADSCs on joint pain and cartilage repair in rats with knee osteoarthritis (KOA). Methods CD146-AMs were prepared and analyzed in materialistic characterization tests. Subpopulations of CD146 + ADSCs were sorted using CD146-AMs. Surface labeling, viability, and proliferation of a subpopulation of CD146 + ADSCs were evaluated in vitro. Molecular characterization of mRNA and protein expression profiles was analyzed by microarray. A rat KOA pain model was established by the iodoacetic acid method, and KOA pain and the promotion of cartilage repair were assessed after treatment with bilateral joint cavity injections of CD146 + ADSCs. Results The CD146-AMs prepared in this study had an average particle size of 242.63 ± 6.74 nm, an average potential of 33.82 ± 3.53 mv, and high CD146 targeting and low cytotoxicity. The positive rate of enriched CD146 + ADSCs was 98.21% and showed a high level of stem cell marker expression and good cell viability. Gene and protein expression profiles showed that CD146 + ADSCs have different cellular functions, especially in regulating inflammation. In the KOA model, low, medium and high concentrations of CD146 + ADSCs were able to improve KOA pain and promote cartilage repair in a concentration-dependent trend. Conclusions The CD146-AMs prepared in this study were able to safely and efficiently sort out the CD146 + ADSCs subpopulation. The subpopulation of CD146 + ADSCs has a unique molecular profile that ameliorates KOA pain and repairs cartilage damage in rats, providing a new idea for KOA treatment.